MANAJEMEN E-LEARNING PRA-PANDEMIC 2021 - Nurhajar Nurhajar (Institut Agama Islam Negeri (IAIN) Palopo, 2021)
Prior to the pandemic of Covid-19 in 2019, e-learning already implemented to replace or combine with face-to-face learning at universities. Some researchers have argued that e- learning can enhance student learning experiences and therefore, motivated policy makers to design more quality teaching and learning in higher education. This study is a pre-pandemic study of e-learning that helped understand its implementation and aims to describe the implementation in an Islamic Religious Higher Education institution. This research deploys quantitative method with pedagogical, sociological and managerial approach to explore the perceptions of e-learning management among the managers. Paper based questionnaires were distributed to seventeen the heads of the departments at the institution to collect the data. The managers shared their understanding on important factors for enhancing e-learning quality within the information technology infrastructure, content management, design funding, academic policy and learning system. The managers’ views of the e-learning enhancing factors were presented further in this paper.